Agenda governamental e políticas públicas: um comparativo das policy communities da educação superior dos governos de Lula a Bolsonaro (2003 - 2022) - Oliveira, Janaina [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This report presents the results of teaching, research, and outreach activities carried out during the postdoctoral program at Unesp, under the PROPG/PROPe Call 06/2024. Regarding the research component, this study aimed to analyze the formulation of public policies for higher education in Brazil between 2003 and 2022, as a continuation of previous investigations, with particular focus on the role of policy communities in shaping the governmental agenda during the Bolsonaro administration (2019–2022). The National Congress (Chamber of Deputies and Federal Senate) served as the primary locus of investigation, based on public hearings (2003–2022), employing content analysis techniques supported by qualitative analysis with NVivo 14 software. This tool enabled data organization, the creation of analytical categories, and the visualization of discursive patterns through resources such as word clouds and cluster analysis based on Pearson’s correlation. The policymaking process in education resulted from the interaction of multiple actors who shared values, experiences, and objectives, forming policy communities or informal/institutional networks that influenced decision-making. The findings indicate that the formulation of the educational agenda was shaped by the performance of policy communities composed of parliamentarians, government officials, members of the National Education Council (CNE), researchers, and representatives of civil society. These communities mediated between technical knowledge and political decision-making, fostering the inclusion of issues advocated by actors into the governmental agenda through the construction of narratives and the definition of public policies for higher education.

Este relatório é resultado das atividades de ensino, pesquisa e extensão realizadas durante o pós-doutorado na Unesp referente ao Edital PROPG/PROPe 06/2024. Em relação à pesquisa, este estudo buscou compreender a formulação de políticas públicas para o ensino superior no Brasil entre 2003 e 2022, a partir de uma continuidade dos estudos já realizados, com foco na atuação das comunidades de política na agenda governamental no Governo Bolsonaro (2019-2022). O Congresso Nacional (Câmara dos Deputados e Senado Federal) foi o principal lócus de investigação, a partir das audiências públicas (2003-2022), utilizando técnica de análise de conteúdo por meio de análise qualitativa do software NVivo 14. Esta ferramenta possibilitou a organização dos dados, a criação de categorias analíticas e a visualização de padrões discursivos, por meio de recursos: nuvem de palavras e análise de cluster com base na correlação de Pearson. O processo de construção das políticas educacionais resultou da interação entre múltiplos atores que compartilham valores, experiências e objetivos, formando as comunidades de políticas/redes informais ou institucionais que influenciam o processo decisório. Os resultados apontam que a formulação da agenda educacional foi marcada pela atuação de policy communities compostas por parlamentares, técnicos governamentais, conselheiros do CNE, pesquisadores e representantes da sociedade civil. Estas comunidades exerceram a mediação entre o conhecimento técnico e a decisão política, impulsionando os temas defendidos pelos atores a entrarem na agenda governamental, a partir da construção de narrativas e a definição das políticas públicas para o ensino superior.
Agenda-Setting and Public Policies: A Comparative Study of Higher Education Policy Communities from Lula to Bolsonaro (2003–2022)
Keywords: Agenda governamental; Análise de conteúdo; Ensino superior; Políticas públicas; Governmental agenda; Content analysis; Higher education; Public policies